Reduced cadherin expression associated with resistance to Bt toxin Cry1Ac in pink bollworm. Issue 1 (3rd July 2019) - Fabrick, Jeffrey A; Mathew, Lolita G; LeRoy, Dannialle M; Hull, J Joe; Unnithan, Gopalan C; Yelich, Alex J; Carrière, Yves; Li, Xianchun; Tabashnik, Bruce E
Abstract: BACKGROUND: Better understanding of the molecular basis of resistance is needed to improve management of pest resistance to transgenic crops that produce insecticidal proteins from Bacillus thuringiensis (Bt). Here we analyzed resistance of the pink bollworm ( Pectinophora gossypiella ) to Bt toxin Cry1Ac, which is used widely in transgenic Bt cotton. Field‐evolved practical resistance of pink bollworm to Cry1Ac is widespread in India, but not in China or the United States. Previous work with laboratory‐ and field‐selected pink bollworm indicated that resistance to Cry1Ac is caused by changes in the amino acid sequence of a midgut cadherin protein (PgCad1) that binds Cry1Ac in susceptible larvae. RESULTS: Relative to a susceptible strain, the laboratory‐selected APHIS‐R strain had 530‐fold resistance to Cry1Ac with autosomal recessive inheritance. Unlike previous results, resistance in this strain was not consistently associated with insertions or deletions in the expected amino acid sequence of PgCad1. However, this resistance was associated with 79‐ to 190‐fold reduced transcription of the PgCad1 gene and markedly lower abundance of PgCad1 protein. CONCLUSION: The ability of pink bollworm and other major pests to evolve resistance to Bt toxins via both qualitative and quantitative changes in receptor proteins demonstrates their remarkable adaptability and presents challenges for monitoring and managing resistance to Bt crops. © 2019 Society of Chemical Industry Abstract : Whereas previous characterization of pink bollworm resistance to Cry1Ac involves mutations and/or alternative RNA splicing of a midgut cadherin receptor protein, here we show that cadherin down‐regulation is also important.